Diagnosis for the design for a psychological intervention program for families in high conflict psycho-legal proceedings - Silveira Tus , Anayancy (Consorcio de Universidades Mexicanas A.C., 2017)
The present paper exposes a diagnosis from the perspective of different actors of the justice system and professionals of family psycho-juridical area about the intervention needs for families in high conflict family legal processes that are in psychological attention by judicial order. Diagnosis results reveal the main characteristics of the families that are in these processes. Based on those results an intervention program was designed, which objective is to provide an alternative of psycho-legal intervention under a psychoeducational and social support model to facilitate parent-filial coexistence and favor the adoption of agreements between parents, as well as to benefit the optimal development and psychological well-being of girls, boys, mothers and fathers participants.